Discourse of Marginality: Constructing the Identity of Indigenous Limbu Community in Parajit Pomu’s Ma Dwaaraa Mero Nirmaana [My Creation by Me] - Rai, Jiwan Kumar (JODEM: Journal of Language and Literature, 2024)
Writing from the margin, in Nepali poetry, has been dominant after 2010s. The poets, particularly belonging to marginalized indigenous groups, started articulating the day-to-day life-experiences, myths, and images of indigenous community to construct the discourse of marginalized people. Then, what distinct cultural myths and images they use and why they do so in their writing. Basing on these problems, this article tries to analyze the anthology Ma Dwaaraa Mero Nirmaana composed by Parajit Pomu. In this analysis, only seven poems – “Ma Dwaaraa Mero Nirmaana”, “Shaalika”, “Naayumaa’, “Yupparung”,  “Helukwaa”, “Philingo Phool”, “Maatoko Geeta”,  and “Dhunwaako Aakriti” – have been selected aiming to explore cultural myths, symbols and images of indigenous community, specifically, of Yakthung Limbu people. The selected poems have been interpreted from the theoretical perspective of Cultural Studies, particularly applying Michel Foucault’s concept of discourse, ‘unthought in cogito’ – a discourse of minorities or marginalized groups. Arguing on the notion of discourse, Foucault defines the discourse as a systematic expression that produces specific body of knowledge. Applying the same idea, on the one hand, the articulation of myths and images in the selected poems construct the discourse of the marginalized Limbus, on the other hand, this discourse of marginality defines and produces outshined body of knowledge about the culture of Limbus intending to claim their cultural identity. This article gives insights and opens new avenues to see and understand the distinct cultural world and knowledge about indigenous Limbu people and their cultures that have been hidden behind the mainstream literary works.